PTU-226 Colorectal cancer screening in a moderate risk population; what is the polyp yield and what is the optimum screening interval?. (28th May 2012) - Walshe, M; Moran, R; Swan, V; Trickovic, J; Kelleher, B; MacMathuna, P
Abstract : Introduction: Colorectal cancer (CRC) screening has been shown to reduce mortality from CRC. Many people with a family history of CRC do not satisfy criteria for syndromes such as HNPCC, and fall into a "moderate risk" category. The reported polyp burden in this group is varied, and the optimum screening regimen is controversial. Our aims were (1) to evaluate the polyp yield at screening colonoscopy in a "moderate risk" group (above average, non-HNPCC) in the setting of a family-screening clinic, (2) to compare polyp yield on 2nd screening colonoscopy between patients with and without adenomas on 1st screening colonoscopy, (3) to evaluate the potential for longer screening intervals for patients with no adenomas on 1st screening colonoscopy. Methods: Family cancer history questionnaires were used to generate family pedigrees and identify "moderate risk" individuals using defined criteria. Adenoma yield on initial colonoscopy was evaluated, and comparisons were made between males & females, and subjects older & younger than 50 yrs. Advanced adenomas (AA) were defined as adenomas ≥10 mm, with high-grade dysplasia, or with a villous component. In patients who had >1 colonoscopy, adenoma yield on 2nd colonoscopy was compared between patients with and without adenomas on initial colonoscopy. Results: From a cohort of 2008 individuals in a high-risk family-screening clinic, 971 (48%) have been assigned a "moderate risk" category. Complete data were available for screening colonoscopies in 236 of these; 99 male, 137 female. On initial screening colonoscopy, 17/236 (7%) had AA, and a further 37/236 (16%) had simple adenomas (SA), (total polyp yield 23%). Polyp yield was higher in males (8% AA, 18% SA) vs females (7% AA, 14% SA), and in the >50 yrs (13% AA, 20% SA) vs <50 yrs (3% AA, 13% SA). More than 1 screening colonoscopy was carried out in 127/236 (54%). Of the 30/127 (24%) who had an adenoma on initial colonoscopy, 4/30 (13%) had AA, and a further 7/30 (23%) had SA on 2 nd colonoscopy (mean interval to f/u 3.62 yrs). In the cohort without adenomas at initial screening; 97/127 (76%), only 1/97 (1%) had an AA, and 10/97 (10%) had SA on 2nd colonoscopy (mean interval 4.6 yrs). Conclusion: In this moderate risk group the polyp yield is highest in males, and those >50 yrs. Adenoma at initial colonoscopy was predictive of adenoma detection at 2nd colonosocopy. In contrast, for individuals without adenomas at initial screening, a very low adenoma yield was observed at follow-up screening. Consequently, within this "moderate risk" cohort, the data supports the adoption of differing screening protocols depending on age, gender, and adenoma yield on initial colonoscopy. Competing interests: None declared.